2010
DOI: 10.4103/1817-1737.62472
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter pneumonia: Is the outcome different from the pneumonias caused by other agents

Abstract: BACKGROUND:The principal aim of the present study was to determine whether Acinetobacter spp. pneumonia differs from hospital-acquired pneumonias (HAPs) caused by other agents with respect to therapeutic success and survival rate.METHODS:This study includes 140 adult patients diagnosed with HAPs caused by identified etiologic agents between March 2005 and February 2006. These patients were divided into two groups according to the agent responsible for their infection (Acinetobacter spp. [n = 63] or non-Acineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This finding is in line with previous observational studies that found lower survival in mixed critically-ill patients (12), sepsis (14,17), and influenza A H1N1 respiratory infection (32). In addition, our results confirm that corticosteroids are potentially harmful in less severely ill patients and in those at low risk of death (9,11,14,39,49).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is in line with previous observational studies that found lower survival in mixed critically-ill patients (12), sepsis (14,17), and influenza A H1N1 respiratory infection (32). In addition, our results confirm that corticosteroids are potentially harmful in less severely ill patients and in those at low risk of death (9,11,14,39,49).…”
Section: Discussionsupporting
confidence: 94%
“…Chronically exposed patients tended to show a poorer survival in an univariate analysis (hazard ratio 1.563, 95% confidence interval 0.940-2.599, p = .09) and similar secondary outcomes, except for shorter length of stay in the ICU (13 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] vs. 17 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], p = .050) when compared to acutely exposed patients. We therefore performed another sensitivity analysis on the subset of patients without chronic exposure to corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the mortality-associated risk factors were evaluated by Edis et al, they reported that hypoalbuminemia, steroid use and the use of a mechanical ventilator increased mortality in A. baumannii pneumoniae [18]. If the patients did not receive appropriate antibiotic therapy, the mortality rate was reported to be 5-fold increased in this study.…”
Section: Resultsmentioning
confidence: 50%
“…As the days on mechanical ventilation raises, the incidence of this hospital acquired infection increases (The average is 5-7 days from the initiation of MV) [16]. In the previous studies, the most common causes of HAPs and VAPs were Pseudomonas aeruginosa, Acinetobacter species, and methicillin-resistant Staphylococcus aureus, but recent studies have shown an increase in the prevalence of Klebsiella pneumoniae and Acinetobacter species [11,[17][18][19]. Resistance of AB and KP to Carbapenems is a challenging topic for the clinicians and infectious diseases control teams [11,20].…”
Section: Discussionmentioning
confidence: 99%